2022
DOI: 10.3390/pharmaceutics14051099
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Form II Paracetamol with the Assistance of Carboxylic Acids toward Batch and Continuous Processes

Abstract: Form II paracetamol has captured the interest of researchers due to its improved compressibility. However, its low stability has made it difficult to be produced on a large scale with good reproducibility. In the present study, the selective polymorphic formation of paracetamol was carried out by cooling crystallization with four types of additives: adipic acid, fumaric acid, oxalic acid, and succinic acid. It was found that: (1) the more additives that were added, the higher the probability of forming Form II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Selective crystallization of polymorphs requires the control and manipulation of nucleation and growth processes and may be carried out through the use of additives. 31 Since the cell-free, concentrated fermentation broth contains various impurities such as 1 to 5 wt% residual sugars, other amino acids, <0.1 wt% inorganic salts, and 0.1 to 1 wt% nitrogen source, 46,70,71 the effects of different sugars and amino acids as additives on the polymorphism of l -GLU have been examined in the present study and summarized in Tables 3 and 4. The effects of those sugars are insignificant, although a small amount of α-GLU was detected as reflected by different characteristic peaks of α-GLU at 2 θ = 32.5, 26.7, and 18.3° in the PXRD patterns of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective crystallization of polymorphs requires the control and manipulation of nucleation and growth processes and may be carried out through the use of additives. 31 Since the cell-free, concentrated fermentation broth contains various impurities such as 1 to 5 wt% residual sugars, other amino acids, <0.1 wt% inorganic salts, and 0.1 to 1 wt% nitrogen source, 46,70,71 the effects of different sugars and amino acids as additives on the polymorphism of l -GLU have been examined in the present study and summarized in Tables 3 and 4. The effects of those sugars are insignificant, although a small amount of α-GLU was detected as reflected by different characteristic peaks of α-GLU at 2 θ = 32.5, 26.7, and 18.3° in the PXRD patterns of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of factors, such as supersaturation, temperature, solvent composition, cooling rate, antisolvent addition rate, agitation rate, seeding, additives, and impurities, can have an impact on solution crystallization as well as solutionmediated polymorphic transformations. [28][29][30][31] Besides, the effects of different scales of mixing, which are linked to the rates of addition or feeding and agitation, may be significant on polymorphism, PSD, and co-crystal stoichiometry. [32][33][34] Controlling a specific (metastable) polymorph in certain cases remains challenging because of the limited fundamental understanding of the dominant factors that can affect the mean size and PSD of each polymorph concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, other crystallization methods or approaches are introduced: antisolvent crystallization, ultrasound-assisted crystallization, laser-induced nucleation, crystallization in gels, , and in the presence of additives (including tailor-made or structurally related additives, , polymers , and surfactants) and templates (self-assembled monolayer or other templates). Structurally related additives have been used to obtain metastable forms of paracetamol, para -aminobenzoic acid, benzamide, etc. It has been demonstrated that metacetamol allowed the formation of paracetamol Form II ,, by blocking the growth of Form I via strong adsorption on the main crystal faces .…”
Section: Introductionmentioning
confidence: 99%